Strategy and grand tactics of Napoleon the Great for the 21st century. Issue 2 (4th March 2023) - Ploumis, Michail
Abstract: War technology, as it was tested in the War of Nagorno-Karabakh (2020), demonstrates that future large-scale ground combat in a symmetric theater of war will be planned and commanded in a centralized manner, while firing from modern weapon systems will play the role of force multiplier. Deception, flanking and envelopment tactics, as they were implemented by Napoleon the Great, are expected to reemerge in order to defeat a potential enemy in a world characterized by the Great Power competition. In this context, the necessity for leaderships which will simultaneously operate throughout the levels of warfare (strategic, operational and tactical) becomes apparent. At the same time, the protection and survival of the landpower in the areas of dispersion, the capacity for rapid advancement of the combative formations to the decisive point of engagement and their capability to apply flanking and envelopment tactics, will decide the victor of a potential war.